Implemplementation of Rapid Application Development of Information System For New Student Admission: Case Study at Akademi Komunitas Industri Manufaktur Bantaeng - Muslihi, Muhammad Takdir (Unit Penelitian dan Pengabdian Kepada Masyarakat, AK-Manufaktur Bantaeng, 2024)
The New Student Admission Information System at the Community Academy of Manufacturing Industry Bantaeng aims to facilitate the process of new student registration online. This research employs the Rapid Application Development (RAD) method in its development. The results indicate that the system has been successfully fully implemented after undergoing a series of black box testing with good results. However, some shortcomings such as minor bugs are identified, and future development is expected to involve improving the overall functionality and security of the system.